Evaluation of Halal Assurance System on Goat Milk Products in OPQ MSME, Sleman, Yogyakarta - Wulandari, Septiana Wahyu; Sirajuddin, Muhammad Mar’ie; Qui, Nguyen Hoang (Universitas Ahmad Dahlan, 2022)
OPQ MSME is an industry engaged in processed products derived from fresh Etawa goat's milk, namely powdered goat's milk and caramel candy. Evaluation of halal assurance system based on the HAS 23101 standard was done to maintain the sustainability of the halal process, in accordance with the provisions of LPPOM MUI. The purpose of this research is to analyze the conformity of halal assurance system on powdered goat milk products at MSME OPQ. The method used in analyzing the problem is interview, literature study, documentation and participatory methods. The results showed that the implementation of the halal assurance system was quite appropriate, but there were several things need to be improved, especially halal policy section, halal management team, training and education, internal audit and management review. Obstacle experienced by MSME OPQ in extending the halal certificate was hindered by the renewal regulation which has now moved from MUI to BPJH, therefore MSME OPQ has not yet received the latest information.